2017
DOI: 10.1021/acs.jafc.7b01050
|View full text |Cite
|
Sign up to set email alerts
|

Plant Uptake and Metabolism of Nitrofuran Antibiotics in Spring Onion Grown in Nitrofuran-Contaminated Soil

Abstract: Environmental pollution caused by the discharge of mutagenic and carcinogenic nitrofurans to the aquatic and soil environment is an emerging public health concern because of the potential in producing drug-resistant microbes and being uptaken by food crops. Using liquid chromatography-tandem mass spectrometry analysis and with spring onion (Allium wakegi Araki) as the plant model, we investigated in this study the plant uptake and accumulation of nitrofuran from a contaminated environment. Our study revealed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Studies have shown that plants absorb and accumulate different environmental pollutants from the soil, such as heavy metals, antibiotics, and pesticides [25,26,27]. As Chan et al have demonstrated, the existence of AAs in the cultivated fields in Serbia (Figure 4) [16] raises the concern of whether AAs translocated from the soil into food crops grown in contaminated fields could accumulate in the plants.…”
Section: Uptake and Bioaccumulation In Food Cropsmentioning
confidence: 99%
“…Studies have shown that plants absorb and accumulate different environmental pollutants from the soil, such as heavy metals, antibiotics, and pesticides [25,26,27]. As Chan et al have demonstrated, the existence of AAs in the cultivated fields in Serbia (Figure 4) [16] raises the concern of whether AAs translocated from the soil into food crops grown in contaminated fields could accumulate in the plants.…”
Section: Uptake and Bioaccumulation In Food Cropsmentioning
confidence: 99%
“…Plant metabolites can serve as indicators for minoring the health and environment of plants. 12,13 In comparison to other methods, detection of HLB disease via metabolites would be advantageous for direct sample analysis, primarily as a result of abundant molecular information. 9,14 Among different methodologies used for analysis of metabolites, mass spectrometry (MS) is an excellent analytical platform as a result of its high specificity, sensitivity, and versatility.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Small-molecule metabolites are naturally produced by all living organisms. Plant metabolites can serve as indicators for minoring the health and environment of plants. , In comparison to other methods, detection of HLB disease via metabolites would be advantageous for direct sample analysis, primarily as a result of abundant molecular information. , Among different methodologies used for analysis of metabolites, mass spectrometry (MS) is an excellent analytical platform as a result of its high specificity, sensitivity, and versatility . In recent years, liquid chromatography (LC) and gas chromatography (GC) coupled with MS analysis have been employed to understand the responses of the plant to HLB. ,, However, on the basis of these traditional MS-based methods, direct methods for determining biomarkers of plant tissues pose a challenge, mainly because conventional MS cannot directly analyze raw bulk samples, such as leaves, veins, and fruits.…”
Section: Introductionmentioning
confidence: 99%
“…The overuse of antimicrobials has caused the occurrence of antimicrobial residue and pollution in plants and soil. Previous studies have shown that furazolidone and nitrofurantoin are efficiently metabolized and produce highly persistent metabolites in plants [ 37 ]. Ciprofloxacin and oxytetracycline used in planting vegetables also remain in the soil and the residence time is related to half-life [ 38 ].…”
Section: Resultsmentioning
confidence: 99%